TRENDS IN THE USE OF RESEARCH METHODS TO UNCOVER THE PHENOMENON OF BULLYING IN EARLY CHILDHOOD EDUCATION IN INDONESIA - Pepi Nuroniah; Ratna Anjani; Esya Anesty Mashudi; Fatihaturosyidah Fatihaturosyidah; Yulianti Fitriani (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to explore trends in research methods used in the study of bullying in early childhood education settings. Using content analysis of 40 articles published between 2014-2024. The findings show there is an increasing trend of research on the theme of bullying in early childhood education settings. Descriptive qualitative research is the most widely used method. The results revealed that bullying is influenced by individual factors such as aggressiveness and lack of empathy, families with authoritarian parenting and domestic violence, and schools that lack supervision and have a permissive culture. The impact includes physical, mental, social, and emotional disorders, including depression, low self-esteem, and difficulty interacting. Lack of intervention in schools, as well as the normalization of violence in mass media and digital content, further exacerbates bullying behavior by increasing children's aggressiveness. Therefore, the role of teachers, parents, and communities is crucial in creating a safe environment through anti-bullying policies, social emotional skills training, and interventions for victims and perpetrators.